10-π-Electron arenes à la carte: structure and bonding of the [E–(CnHn)–E]n−6 (E = Ca, Sr, Ba; n = 6–8) complexes. Issue 17 (3rd March 2016) - Mondal, Sukanta; Cabellos, Jose Luis; Pan, Sudip; Osorio, Edison; Torres-Vega, Juan Jose; Tiznado, William; Restrepo, Albeiro; Merino, Gabriel
Abstract : Alkaline earth metals (Ca, Sr, and Ba) can form inverted sandwich compounds with C6 H6, C7 H7 +, and C8 H8 2+ of D n h symmetry holding planar 10-π-electron aromatic cores. Abstract : In this paper, we provide solid evidence to show that among an overwhelming structural diversity, alkaline earth metals (Ca, Sr, Ba) have the ability to form inverted sandwich compounds with C6 H6, C7 H7 +, and C8 H8 2+ of D n h symmetry and general formula [E–(C n H n )–E] n −6 ( n = 6–8) with planar 10-π-electron aromatic cores by virtue of transferring two electrons per metal atom to the ring. However, the origin of the orbital interaction between the metals and the carbon ring is quite different; while [E–(C6 H6 )–E] complexes are dominated by δ-interactions, both π- and δ-interactions are important in [E–(C7 H7 )–E] + and [E–(C8 H8 )–E] 2+ complexes.